Analysing appropriations in a professional development program: How teachers adopt interactional support for developing academic discourse skills in classroom discussions - Morek, Miriam; Heller, Vivien (European journal of applied linguistics, 2025)
In recent years, research on whether and how teachers can be trained to lead productive classroom discussions has increased. However, very little is known so far about how teachers actually adopt new interactional strategies in everyday classroom discussions. The aim of the present paper is to discuss this question based on an empirical study. Drawing on video recorded classroom interactions collected within a teacher professional development program, we examine how teachers of German implement strategies for content-integrated support of discursive learning into everyday classroom discussions. In particular, we focus on how they attempt to establish discursive tasks and multiply opportunities for their students to provide explanations or reasons. Combining methods of conversation analysis and interactional discourse analysis with a language and literacy education perspective, we show that teachers adopt selected aspects of new strategies or use them schematically without integrating them into subject matter learning. We argue that these in-situ adoptions can be understood as instances of appropriation, i.e. as teachers’ productive, focalized experimenting with new interactive strategies. Situated within educational linguistics and linguistic teacher education research, our study thus contributes both to agent-centered research on teachers’ professional development and to the growing body of research on content-integrated language learning.